Towards a needs-based design of the physical rehabilitation workforce in South Africa: trend analysis [1990-2017] and a 5-year forecasting for the most impactful health conditions based on global burden of disease estimates - Q. Louw; K. Grimmer; K. Berner; T. Conradie; D. T. Bedada; T. S. Jesus (BMC, 2021)
Abstract Background Rehabilitation can improve function in many people with chronic health conditions. It is important to consider priority conditions requiring rehabilitation, so it can be realistically positioned and costed in national health financing systems like South Africa (SA)'s proposed National Health Insurance (NHI). This paper describes temporal trends of top-ranked conditions on years lived with disability (YLDs) rates in SA, for which physical rehabilitation can ameliorate associated disability. Methods This study is a systematic synthesis of publicly available Global Burden of Disease (GBD) 2017 estimates. The top 11 conditions contributing most to YLDs and for which evidence-based rehabilitation interventions exist were identified. Age-standardized rates per 100,000 and YLDs counts were extracted from 1990 to 2017. Significance of changes in temporal trends was determined using Mann-Kendall trend tests. Best-fit rates of yearly changes were calculated per condition, using GBD estimates (2012-2017), and extrapolated (by imposing the best-fit regression line onto results for each subsequent predicted year) as forecasts (2018-2022). Results Trends for YLDs counts per condition year (1990-2017) and forecasted values (2018-2022) showed an overall steady increase for all conditions, except HIV and respiratory conditions. YLDs counts almost doubled from 1990 to 2017, with a 17% predicted increase from 2017 to 2022. The proportionate contribution to YLDs counts reduced over time for all conditions, except HIV. Although age-standardized YLDs rates appear relatively stable over the analyzed periods for all conditions (except HIV, respiratory conditions and type 2 diabetes), trend changes in YLDs rates over 28 years were significant for all conditions, except neonatal (p = 0.855), hearing loss (p = 0.100) and musculoskeletal conditions (p = 0.300). Significant trend decreases were apparent for 4/9 conditions, implying that another 5/9 conditions showed trend increases over 28 years. Predicted all-age prevalence in 2022 suggests relatively large increases for cardiovascular disease and heart failure, and burns, while relative decreases are predicted for fractures and dislocations, stroke, and musculoskeletal conditions. Conclusion Rehabilitation needs in SA are potentially massive and unmet, highlighting the need for innovative and context-specific rehabilitation that considers current local needs and projected changes. These findings should be considered when designing the NHI and other schemes in SA to ensure human and financial resources are deployed efficiently.